2017
DOI: 10.1093/ofid/ofx199
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Seminal HIV-1 RNA Load After Praziquantel Treatment of Urogenital Schistosomiasis Coinfection in HIV-Positive Men—An Observational Study

Abstract: BackgroundUrogenital schistosomiasis due to Schistosoma hematobium infection is hypothesized to cause increased HIV-1 RNA shedding in semen in HIV co-infected men as result of chronic egg-induced inflammation in the prostate and the seminal vesicles. The effect of treatment with the antihelminthic agent praziquantel on seminal HIV-1 RNA load was assessed in this study.MethodsHIV-1 RNA load was determined in blood plasma and semen at baseline and at 10-week follow-up. Praziquantel was administered at baseline a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…These cytokines can facilitate HIV replication, which can increase seminal viral shedding, alluding to a plausible additional risk of HIV transmission from males infected with HIV and urogenital schistosomiasis. [19][20][21] Examples such as Case 2 describing the coinfection of these two diseases could in future provide opportunities for further virological and immunological analyses to illustrate the impact of routine preventive PZQ treatment on the potential risk of HIV transmission among dually infected fishermen and other high-risk populations in endemic areas. Furthermore, additional diagnostic investigations to exclude other diseases such as STIs, which could be present in this case, would be informative.…”
Section: Discussionmentioning
confidence: 99%
“…These cytokines can facilitate HIV replication, which can increase seminal viral shedding, alluding to a plausible additional risk of HIV transmission from males infected with HIV and urogenital schistosomiasis. [19][20][21] Examples such as Case 2 describing the coinfection of these two diseases could in future provide opportunities for further virological and immunological analyses to illustrate the impact of routine preventive PZQ treatment on the potential risk of HIV transmission among dually infected fishermen and other high-risk populations in endemic areas. Furthermore, additional diagnostic investigations to exclude other diseases such as STIs, which could be present in this case, would be informative.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of bacterial STI with antibiotics significantly decreases the concentration of HIV-1 RNA in seminal plasma ( Cohen et al., 1997 ). Similarly, African men with genital schistosomiasis showed a decline in the concentration of HIV-1 RNA in seminal plasma after treatment with praziquantel ( Midzi et al., 2017 ). Immunologically, egg-positive schistosome infection induces a strong Th2 bias ( Pearce et al., 1991 ).…”
Section: Does Fgs Behave Like An Sti or Bacterial Vaginosis In Heteromentioning
confidence: 99%
“…Furthermore, leucocytospermia and high seminal levels of inflammatory cytokines as seen in men with urogenital schistosomiasis actually normalize after treatment of schistosomiasis with praziquantel [27]. A recent prospective clinical study assessed the effect of praziquantel treatment on HIV-1 RNA load in blood plasma and semen of HIV-infected men from Zimbabwe co-infected with urogenital schistosomiasis [28]. The study demonstrated a decline of seminal HIV-1 RNA load following praziquantel treatment.…”
Section: Trematodesmentioning
confidence: 99%